SISTEM INFORMASI PEMBELIAN BAHAN BAKU SEPATU PADA DIVISI NIKE BAGIAN PURCHASING DI PT. NIKOMAS GEMILANG - Elan Mailiyanto; Ahmad Rufai; Ahmad Jaka (Amal Insani Foundation, 2022)
This research aims to analyze and design the IYCOST information system currently running within the company. Implementing the raw material purchasing process to control the availability of raw materials in the purchasing process must be based on what has been determined by the company at PT. Nikomas Gemilang, in carrying out research, the PIECES research method provides a clear picture of the state of the company in relation to the problem under study. Data collection techniques used to obtain primary data were carried out using observation and interviews, and to obtain secondary data, library research was used. This research's results indicate the purpose of purchasing raw materials at PT. Nikomas Gemilang is to control every process of purchasing raw materials, both raw materials that will and have entered the warehouse. The availability of the raw materials needed is by the SOP (Production Operational Standards), which requires that the purchasing department be able to provide raw materials. In addition to being effective and timely, they must also be of good quality in managing PT. Nikomas Gemilang uses an information system called IY COST, where PT. Nikomas Gemilang consistently innovates on existing systems; in addition to increasing the convenience of each system user, it can also reduce unexpected planning costs in purchasing raw materials determined by the centre of Taiwan.